Designing an e-report system as a digital portfolio in early childhood education in Surabaya using the waterfall method - Alifkhan, Mochammad Vaif Dwi; Laga, Sinarring Azi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This study focuses on the design and implementation of an E-Report system as a digital portfolio for Early Childhood Education in Genteng District, Surabaya. The current manual process using Excel and Canva for generating learning reports limits efficiency and accuracy in tracking children’s developmental progress. To address this, a web-based E-Report system was developed using the Waterfall method to streamline reporting processes, allowing educators to manage children’s data digitally while providing parents accessible, real-time progress reports. Development stages included requirement analysis, system design, and implementation, leveraging modern web technologies for optimal performance. User satisfaction assessments reveal high satisfaction levels, particularly in the system's format (average score of 3.80) and content (average score of 3.65), indicating a strong alignment with user needs. The implementation of the E-Report system is expected to elevate Early Childhood Education services in Genteng District by delivering a more efficient, accurate, and collaborative reporting tool.